2018
DOI: 10.1103/physrevapplied.10.054046
|View full text |Cite
|
Sign up to set email alerts
|

Near- Tc Ferromagnetic Resonance and Damping in FePt -Based Heat-Assisted Magnetic Recording Media

Abstract: High-temperature ferromagnetic resonance (FMR) in FePt-based media materials was studied for the first time. The FMR linewidth (ΔH) as a function of temperature (T), field angle (θ H), and the volume fraction (x) of carbon in the material were determined, and the effective Gilbert damping constant and the Bloch-Bloembergen relaxation time were estimated. The data suggest that at temperatures 10-45 K below the Curie temperature, two-magnon scattering and spin-flip magnon-electron scattering make comparable cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
5
14
1
Order By: Relevance
“…Clearly, the magnon contributions to the damping give rise to an increase of the damping with increasing temperature, which is inconsistent with the results of Richardson et al [15]. However, the experiments described in ref [15] give the temperature dependence of the linewidth which likely has contributions from inhomogeneous line broadening arising from dispersion of magnetic properties. In the following we develop a model accounting for the inhomogenous line broadening which gives good qualitative agreement with the experiments.…”
Section: Grid-search Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…Clearly, the magnon contributions to the damping give rise to an increase of the damping with increasing temperature, which is inconsistent with the results of Richardson et al [15]. However, the experiments described in ref [15] give the temperature dependence of the linewidth which likely has contributions from inhomogeneous line broadening arising from dispersion of magnetic properties. In the following we develop a model accounting for the inhomogenous line broadening which gives good qualitative agreement with the experiments.…”
Section: Grid-search Methodsmentioning
confidence: 70%
“…It is important to note that these values include both intrinsic and extrinsic contributions, the purely intrinsic damping being even smaller than the reported values [13,14]. Recently, Richardson et al [15] reported experimental measurements of damping at elevated temperatures showing an unexpected decrease of damping with temperature. A decrease in the effective damping can be crucial in HAMR, as this can increase the switching time, affect the signal to noise ratio and negatively impact the performance of HAMR.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The FMR measurements included (1) frequencydependent FMR measurements using a co-planar waveguide (CPW) and a vector network analyzer (VNA) at room temperature 16 , 17 and (2) temperaturedependent FMR measurements using a microwave cavity. 18 Figure 2 shows the experimental configuration and representative data for frequencydependent FMR measurements. Figure 2(a) sketches the experimental setup, which consists mainly of a CPW device and a VNA.…”
Section: Broadband Fmr Approachmentioning
confidence: 99%
“…More details about this approach are provided in Ref. [18]. Figure 4(b) presents the FMR data (blue dots) measured at T=373 °C on a sample where the soft layer was made of a 5.0-nm-thick Co film.…”
Section: High-t Fmr Approachmentioning
confidence: 99%